2003
DOI: 10.1097/01.blo.0000069891.31220.fd
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Pelvic Flexion Angle Using Three-Dimensional Computed Tomography

Abstract: The purpose of the current study was to evaluate whether safe acetabular component position depends on differences in pelvic location between the supine, standing, and sitting positions. The subjects of the current study were 101 patients who had total hip arthroplasty. Anteroposterior radiographs of the pelvis with the patients in the supine, standing, and sitting positions were obtained preoperatively and 1 year after total hip arthroplasty. Computed tomography images of the pelvis were obtained preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
215
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 246 publications
(240 citation statements)
references
References 13 publications
18
215
2
5
Order By: Relevance
“…Lembeck et al, in their cohort, observed a range of supine pelvic tilt from À17°to 3°, and standing pelvic tilt ranged from À27°to 3° [32]. Patients with hip disorders similarly have a wide range of individual pelvic tilt measurements [10], ranging greater than 60°in one study [39]. We (1) asked if acetabular anteversion measurements using the femoral head centers differed from those using the posterior ischia and (2) sought to understand the effects of changing obliquity, rotation, and tilt of a pelvis in a CT scanner on the measurement of acetabular variables.…”
Section: Discussionmentioning
confidence: 86%
“…Lembeck et al, in their cohort, observed a range of supine pelvic tilt from À17°to 3°, and standing pelvic tilt ranged from À27°to 3° [32]. Patients with hip disorders similarly have a wide range of individual pelvic tilt measurements [10], ranging greater than 60°in one study [39]. We (1) asked if acetabular anteversion measurements using the femoral head centers differed from those using the posterior ischia and (2) sought to understand the effects of changing obliquity, rotation, and tilt of a pelvis in a CT scanner on the measurement of acetabular variables.…”
Section: Discussionmentioning
confidence: 86%
“…Allocations of acetabular surface particularities or lesions were given either with reference to the acetabular incision [4,6,35,39,55,66] or in relation to the vertical axis of the patient as seen during surgery [30,38,58]. The individual acetabular tilt and variations in pelvic tilt [2,10,12,32,33,41,48,57] complicate comparison of these data.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from variations in pelvic tilt [2,10,12,32,33,41,48,57], this can now be explained by variations of acetabular tilt, which influences spatial positions of peaks and depressions along the rim. The results of our measurements for version are comparable to other anatomical studies (Table 8).…”
Section: Discussionmentioning
confidence: 99%
“…Imageless navigation referencing techniques do not appear to be process-capable using Six Sigma formulas and those findings held up in the current study. Although studies have shown pelvic tilt may be an equal factor determining functional acetabular component positioning, the goal of the current study was to assess the effectiveness of various methods to position the acetabular component with two degrees of freedom in relation to the APP [24,26,28]. In practice, the imageless CAS referencing technique currently uses a direct anatomic point matching method.…”
Section: Discussionmentioning
confidence: 99%